(untitled) (Cardiovascular Journal, 2014)
Arrow injury in the neck with subsequent pseudoaneurysm formation of the brachiocephalic artery is an uncommon type of injury in our country. Initially it was a punctured wound in the neck which was simply repaired. About 13 days after the initial injury patient came back to hospital with severe respiratory distress and backache for which emergency tracheostomy was needed. This simple puncture wound subsequently developed haematoma in the neck and two pseudoaneurysms at distal brachiocephalic artery. CT angiogram was very helpful to confirm the diagnosis. Correct referral to tertiary hospital like National Institute Cardiovascular Diseases (NICVD) ,prompt diagnosis, definitive treatment of the injury and subsequent aggressive postoperative management saved the life of this young tailor. DOI: http://dx.doi.org/10.3329/cardio.v7i1.20802 Cardiovasc. j. 2014; 7(1): 58-62